(untitled) (Proceeding Of Sari Mulia University Midwifery National Seminars, 2024)
Background: In order to recover, the diet provided must be of high quality with sufficient calories, protein, fluids, and plenty of fruits. However, several factors, including cultural aspects, influence postpartum mothers to undergo behavioral changes regarding dietary taboos that should actually be encouraged. Objective: This study aims to determine how the Relationship Between Knowledge About Nutrition Fulfillment and Dietary Taboo Behavior Among Postpartum Mothers can occur in Murung Karangan Village, Muara Harus Sub-District, Tabalong District. Method: This research used a quantitative approach with cross-sectional design. The population consisted of all postpartum mothers who followed dietary taboos in Murung Karangan Village, selected through total sampling. Results: There was no significant relationship between the level of knowledge and dietary taboos among postpartum mothers. Using the Chi-Square test at alpha 0.05, the value obtained was 0.317 (p > 0.05), which means statistically, the null hypothesis (Ho) is accepted. Conclusion: The majority of postpartum mothers adhere to dietary taboos due to behavioral, cultural, hereditary advice from parents, and personal beliefs, as well as the knowledge about dietary taboos they possess